Empowerment Model of Farmers Group Association (Gapoktan) as a Delivery Point for Subsidized Fertilizer In Several Large Areas Increase Planting (LTT), and Optimize Land (OPLAH) Indonesian Rice Fields - Effendy, Lukman; Haryanto, Yoyon; Rusmono, Momon; Pratiyanto, dan Arif (Technium Sustainability, 2025)
A series of research to detect the readiness of the Association of Farmer Groups (Gapoktan) as a delivery point for subsidized fertilizer in accordance with Presidential Regulation of the Republic of Indonesia Number 6 of 2025 has been carried out in several areas for the rice planting area (LTT) and land optimization (OPLAH) program. Specifically, this research aims to: 1) describe variables related to the role of Gapoktan as a handover point, 2) analyze the factors that influence Gapoktan’s role as a handover point, and 3) formulate a strategy to increase Gapoktan’s role as a handover point. The research applied a survey method to 240 GAPoktan member farmers in the LTT and OPLAH areas from 15 districts and five provinces, namely: West Java, Lampung, South Sumatra, Jambi and South Kalimantan. Determination of respondents is based on each district’s quota. Data was collected using a questionnaire that had been tested for validity and reliability. Data analysis uses Samrt-PLS analysis. The research results show that Gapoktan’s empowerment is influenced by environmental factors (X3) and needs factors (X4). Environmental factors are determined by community perception, availability of facilities and infrastructure, and support from parties, while need factors are determined by social needs, the need for achievement and the need to participate in development.